NHC‐catalyzed Redox‐Neutral Aza‐Benzoin Reaction of Aldehydes with Tetrahydroisoquinolines. Issue 2 (24th December 2019) - Jiang, Di; Wu, Zijun; Wang, Jian
Summary of main observation and conclusion: Tetrahydroisoquinoline derivatives are useful synthetic intermediates, which play an important role in the preparation of natural products, pharmaceuticals and other materials. Herein, we report an unprecedented redox‐neutral aza‐benzoin protocol to construct such scaffold. Upon exposure of tetrahydroisoquinolines to aromatic aldehydes in the presence of an NHC catalyst, the C‐1 acylated tetrahydroisoquinolines were obtained in moderate to good yields. Abstract :